Evaluation of 940 nm Diode Laser in Esthetic Crown Lengthening - Ali, Noor; Dhahir, Mohammed; Aldelaimi, Tahrir (Iraqi Journal of Laser, 2023)
Abstract Background: Crown lengthening is a surgical procedure that apically positions the gingival edge and/or removes supporting bone in order to increase the amount of supra gingival tooth structure for restorative or cosmetic purposes. The objective of the study: The purpose of this study was to evaluate the efficacy of the 940nm diode laser in esthetic crown lengthening surgery through clinical observations, patient questionnaires, clinical photographs, and gingival healing following gingival operations. Material and methods: In this randomized clinical trial, 16 patients (11 females and 5 males) had their crowns surgically lengthened using a diode laser (940 nm) in continuous wave (CW) mode with 1 watt energy settings. A visual analogue scale is used on the first, third, seventh, and twenty-first days following surgery to record pain, swelling, bleeding, functional interference, tooth sensitivity, and success from an aesthetic standpoint, as well as overall patient satisfaction based on patient opinion and clinical photographs. Results: In the present study, we noticed that the scale of pain, bleeding, oedema, function interferance, and tooth sensitization significantly decreased gradually during the first two visits. The measured parameters completely disappeared after one week in most cases, as well as increase patient satisfaction and aesthetic achievement. The patients were recalled three weeks later, the wounds had totally healed, and the patient were not complaining of any pain. Conclusion: Crown lengthening requires optimal gingival margin design. This involves precise shaping of delicate tissues, which is difficult with the scalpel. While Lasers give improved gingival sculpting control and can be used for aesthetic crown lengthening. The laser surgery has many advantages, including excellent hemostasis with little or no bleeding, being less invasive and sterile wound cut, causing less pain and suffering during and after surgery, and enhancing patient satisfaction since the operation is short and, in most circumstances, relatively painless. Also, in laser surgery, there is less functional interruption and enhanced patient satisfaction since a periodontal pack is not needed to cover the surgery site. The healing is faster and more aesthetic when using laser surgery procedure.